Pengiriman Citra pada Komunikasi Cahaya Tampak IEEE 802.15.7 Lapisan Fisik II.f-n - Eny Sukani Rahayu; Rabani Rashif Saniy Alfarisi; Iswandi (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2016)
Visible light communication (VLC) is a communication technology using visible light as a transmission medium that can have larger bandwidth than other wireless communications. VLC has a standard of IEEE 802.15.7 which has two layers. One of the layers is Physical Layer (PHY) II which has characterictic for indoor and line of sight communication. In this layer, the standard for data rate and optical clock rate is higher than the other types of layers using on off keying (OOK) modulation. This research investigated variation effect of clock rate, data rate, and Reed Solomon (RS) coding to bit error rate (BER) of the received signal. Nowadays, mostly data are pictures and videos. So, this research also test the VLC PHY II to transmit a picture under the varied conditions using peak signal to noise ratio (PSNR). All investigations are built in simulation. The results show that the lower RS coding rates, the lower BER values, and the higher optical clock rate, the higher data rate obtained. Good quality of picture is obtained with BER 10-4 and PSNR 39 dB.